Delineating structural features of North Cameroon using the EIGEN6C4 high‐resolution global gravitational model. Issue 10 (5th July 2022) - Ghomsi, Franck Eitel Kemgang; Pham, Luan Thanh; Steffen, Rebekka; Ribeiro‐Filho, Nelson; Tenzer, Robert
Abstract : The Cretaceous basins of the West and Central African Rift System (WCARS) are characterized by sinistral strike–slip movements observed between the Benue and Arabian–Nubian microplates. These basins share a similar basin‐filling structure, history, and tectonic processes. They have attracted a significant interest in the study of their geodynamics and subsurface structure through geophysical exploration methods. Nevertheless, North Cameroon located in this microplate confluence has not yet been investigated in terms of identifying geological structures, such as lineaments and faults. To contribute to a better understanding of the northern Cameroon structural framework and its tectonic context, we investigate the lineaments in northern Cameroon by using the EIGEN‐6C4 gravitational model and a variety of recent processing techniques (Tilt derivative [TDR], Theta Map [TM], Horizontal tilt angle [TDX], and Edge Detector [ED]). Our results show that the lineaments are trending in ENE–WSW, NW–SE, NE–SW, and WNW–ESE directions. These directions are consistent with the Cretaceous Garoua Rift and granitoids of the Cameroon‐Chad line. The presented result clearly delineates continuous architectonic features of the structural edges of the Saharan Metacraton, the Cretaceous Garoua Rift, the Bibemi‐Léré granitoids, and the Adamawa faults. Abstract : North Cameroon lies on the northern edge of the Archean Congo Craton, east of the West African Craton and bisected by the Saharan Metacraton. The application of a global gravity model in this region has provided a significant and unprecedented geotectonic advantage through the application of recent edge filters.